Microbial solutions must be deployed against climate catastrophe - Raquel Peixoto; Christian R. Voolstra; Lisa Y. Stein; Philip Hugenholtz; Joana Falcao Salles; Shady A. Amin; Max Häggblom; Ann Gregory; Thulani P. Makhalanyane; Fengping Wang; Nadège Adoukè Agbodjato; Yinzhao Wang; et al. (npj Biofilms and Microbiomes, 2024)
This paper is a call to action. By publishing concurrently across journals like an emergency bulletin, we are not merely making a plea for awareness about climate change. Instead, we are demanding immediate, tangible steps that harness the power of microbiology and the expertise of researchers and policymakers to safeguard the planet for future generations.